SELF-ACTUALIZATION IN IWAN SIMATUPANG’S NOVEL ZIARAH - Manugeren, M. (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
A person should achieve maximum satisfaction in life and achieve balance between physical, emotional, social and spiritual aspects as the manifestation of self-actualization. This research aims to reveal that an individual who experiences a self-actualization process is able to recognize and develop their talents, abilities and values. The entire research is carried out using a qualitative descriptive method to reveal that self-actualization can be used as a guide to achieving harmony between all elements of the environment. In the data collection  procedures, all the data with a focus on self-actualzation are gathered from the novel, covering a comprehensive data selection to meet the objectives of the study. The selected data are then sorted  out to be conformed with the types of self-actualization as the points of analysis. For the data analysis, deductive frequency method of analysis is applied, going from general to specific analysis. All the types of data needed are classified, coded and  interpreted comprehensively based on the focus of the study. The main data source is obtained from the novel above and subsequently from other related references. By using a humanistic psychology approach with the concept of the process of self-understanding which is then generated with the theory of human needs by Abraham Maslow, with a formulation of the levels of human needs starting from the most basic to gaining self-understanding, it is found that the novel contains the concept of self-actualization in the form of free will, responsibility and self-awareness.